International comparison of guidelines for managing neonates at the early phase of the SARS-CoV-2 pandemic - Lavizzari, A; Klingenberg, C; Profit, J; Zupancic, JAF; Davis, AS; Mosca, F; Molloy, EJ; Roehr, CC (Springer Nature, 2020)
Background: The COVID-19 pandemic threatens global newborn health. We describe the current state of national and local protocols for managing neonates born to SARS-CoV-2-positive mothers.